Utilidad de los ultrasonidos en urología. - Espuela Orgaz, R.; Guinda Sevillano, C.; Martínez Pérez, E.; Nogueras Gimeno, M.A.; Perea Arbej, J.A.; Arnaiz Esteban, F. (Clínicas Urológicas de la Complutense, 1994)
Sin resumen